DEVELOPING A CHILD'S AUTHENTIC LEARNING EXPERIENCE THROUGH MEDIA: TEACHERS' APPROACH - Braslauskienė, Rasa; Jacynė, Reda; Vaičiulė, Rosita (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The article analyses the development of an authentic experience for primary school students as a result of experiential learning. Possibilities of developing children’s authentic experience through media are discussed, as the ability to find, perceive and critically assess and use information and media content, as well as to express oneself, are one of the most important human abilities in the 21st century. The article presents a qualitative research of the attitudes of primary education teachers about the development of a child’s authentic experience by using media. The following research revealed that the method of accumulating authentic experience has a positive effect on students’ learning motivation, allows to develop critical, creative thinking, constructs a real connection with teaching materials and practice, enables students to operate actively, independently, and be responsible for their own learning. The research highlighted the advantages and disadvantages of developing an authentic learning experience through media.